Revit 2017 Essential Training: MEP (Metric). - Wing, Eric (linkedin.com, 2016)
Learn about MEP design in Revit 2017. Explore the four major trades of MEP engineering: mechanical, electrical, plumbing, and fire protection by reviewing examples in metric units.